2023
DOI: 10.3390/foods12081690
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nutraceutical Composition Based on Fermented Spirulina, Apple Cider Vinegar, Jerusalem Artichoke, and Bovine Colostrum

Abstract: The main purpose of this experiment was to develop a multifunctional nutraceutical composition based on ingredients of different origins (Spirulina powder (SP), bovine colostrum (BC), Jerusalem artichoke powder (JAP), and apple cider vinegar (ACV)) which possess different health benefits through their different mechanisms of action. In order to improve the functional properties of Spirulina and bovine colostrum, fermentation with the Pediococcus acidilactici No. 29 and Lacticaseibacillus paracasei LUHS244 stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In recent years, fermentation technologies based on the inoculation of various probiotic bacteria like Lactiplantibacillus plantarum (Lp. Plantarum) have played an important role in lowering antinutritional factors and increasing the nutritional profiles of fermented goods [ 12 , 13 , 14 , 15 , 16 ]. However, data on the application of microbial strain (starter cultures) like Lp.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fermentation technologies based on the inoculation of various probiotic bacteria like Lactiplantibacillus plantarum (Lp. Plantarum) have played an important role in lowering antinutritional factors and increasing the nutritional profiles of fermented goods [ 12 , 13 , 14 , 15 , 16 ]. However, data on the application of microbial strain (starter cultures) like Lp.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of lactic acid bacteria (LAB) to ferment the rich variety of carbohydrates in food raw-materials determines their key role in the food industry for the production of a variety of fermented products of plant and animal origin [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Fermented foods make up about a third of the human diet [ 8 , 9 ], and lactic acid fermentation, in particular, is one of the oldest approaches to improve the nutritional value and organoleptic characteristics of raw-materials, to extend their shelf-life and save energy in the preparation of plant-based foods, including bread and other baking goods [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that fermentation with selected lactic acid bacteria (LAB) strains can be applied to reduce undesired microorganisms present in bovine colostrum (microbial decontamination) [14], as well as to drive out to a broader spectrum of antimicrobial properties in this valuable and prospective food or supplement ingredient [15]. Indeed, technologically functionalized colostrum can be successfully applied to the development of attractive, functional product formulations [16][17][18].…”
Section: Introductionmentioning
confidence: 99%